Novel analytical parameter extraction for SiGe HBTs based on the rational function fitting. (April 2015) - Sun, Yabin; Fu, Jun; Yang, Ji; Xu, Jun; Wang, Yudong; Zhou, Wei; Zhang, Wei; Cui, Jie; Li, Gaoqing; Liu, Zhihong
Highlights: Several expressions for related Y -parameter frequency response are derived in the form of non-linear rational function. Eight constant terms are simultaneously obtained as a result of the non-linear rational function fitting. The circuit elements are accurately extracted in an analytical closed-form manner based on the rational function fitting. Proposed method is validated and the simulated S -parameter match well with the measured data in desired frequency range. Abstract: A novel analytical direct parameter extraction technique for the small-signal equivalent circuit of SiGe HBTs under forward-active-mode operation is presented in this paper. After the extrinsic collector resistance and substrate-network elements removed from the measured S -parameter, several expressions for the related Y -parameter frequency response are derived in the form of rational functions and eight constant terms are simultaneously obtained. The circuit elements are then accurately extracted in an analytical closed-form manner based on the non-linear rational function fitting of device frequency response across the whole frequency range, without any numerical optimization or approximation. The proposed technique is successfully validated to SiGe HBTs with different device sizing and bias conditions from 100 MHz to 20.89 GHz, and the simulated S -parameters match well with the measured data in the desired frequency range.